Formalizing and checking web service discovery models using B. - Thuan, Truong Ninh; Binh, Trinh Thanh; Hieu, Vu Van (Journal of Computer Science and Cybernetics, 2012)
The impact of formal methods in service oriented architecture (SOA) has been well-known because of its capability for verification and early analysis of the feasibility. This paper proposes an approach to formalize and analyze the conformance between requirements of web service requester desired and capabilities of web service provided. The requirements of service requester, including functional and non-functional properties, are modeled by a B abstract machine and capabilities of service provider, described by OWL-S, are formalized by a B refinement machine. The matching between these two sides of web service discovery models is analyzed by B support tools.